Seed priming and exogenous application of citric acid enhance seedling growth and photosynthetic pigments and mitigate oxidative damage of soybean (Glycine max) under salt stress - Imran, Shahin; Mahamud, Md. Asif; Paul, Newton Chandra; Chakrobortty, Jotirmoy; Sarker, Prosenjit; Paul, Shipan; Tahjib-Ul-Arif, Md.; Rhaman, Mohammad Saidur (Archives of Biological Sciences, 2023)
Paper description: Soybean is an important crop whose seed germination, seedling growth, and physiological and biochemical traits are hampered by salinity. Petri dish and hydroponic pot experiments were conducted using BARI Soybean-6 variety to examine the salinity stress mitigating effect of citric acid. Citric acid increased germination, growth, and photosynthetic pigments, and decreased H2O2 and malondialdehyde (MDA) contents caused by salinity stress. The results of this study may be useful in reducing salinity stress-induced growth inhibition of different crops like soybeans on saline areas in coastal belts and maximizing their potential as agricultural lands. Abstract: Seed priming and citric acid (CA) supplementation on germination and seedling growth of soybeans were investigated. Soybean seeds were primed with distilled water (control), 1 mM CA (CA1), or 2 mM CA (CA2) and then placed for germination in Petri dishes containing distilled water or 150 mM NaCl (SS), alone or in combination with 1 mM or 2 mM CA. Germinated seeds were placed in hydroponic pots using a similar treatment regimen to that specified for the Petri dishes to obtain seedling growth and biochemical parameters. Salt stress significantly lowered germination, growth traits, relative water content (RWC), and photosynthetic pigment. When soybean seeds were primed with CA under salt stress, the germination rate, final germination percentage, seed vigor index, and number of lateral roots significantly increased. Moreover, supplementation of CA significantly increased fresh and dry shoot and root weight, plant height, RWC, and photosynthetic pigments compared to salt-treated plants. The results also displayed that salt stress considerably increased hydrogen peroxide (H2O2) and malondialdehyde (MDA) contents compared to control plants. Spraying of CA1 and CA2 significantly lowered the levels of H2O2 and MDA in salt-treated plants. Both hierarchical clustering and PCA revealed that the effects of salt stress and CA on germination, growth characteristics, photosynthetic pigments, H2O2, and MDA concentrations strongly interacted with one another. According to the findings, CA could be applied as a seed priming and exogenous agent to help soybeans grow more quickly when exposed to salt stress.